RUISLAG TANAH WAKAF PERSPEKTIF IMAM AS-SYAFI’I: Kasus di Mushola Abdurrahman Al Jamil Bumen Bumirejo Kab. Wonosobo - Luhfiana, Mia; Bashori, Akmal (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2023)
Waqf is a form of Islamic socio-religious worship which is highly recommended for Muslims, because waqf will always distribute rewards to those who donate it even though the person concerned has died. While swapping waqf is replacing the waqf property with other assets because there is benefit or indeed it must be replaced which in Islam is known as istibdal. The problems examined in this study are first, how is the practice of implementing swaps for waqf land at the Andurrahman al Jamil prayer room in Bumen Hamlet, Bumirejo Village, Mojotengah District, Wonosobo Regency. Second, how is the law of the swap practice from the perspective of Imam As-Shafi'i. to find out whether the practice of swapping is in accordance with the As-Shafi'i Madzhab or not. This research uses field research methods with data analysis and processing on objects that compare the law of Imam As-Syafi'i with the practice of swapping rolls that occur in the Bumen, Bumirejo, Mojotengah, Wonosobo neighborhoods. The results of the first study show that in the practice of exchanging waqf land that took place at the Abdurrahman Al Jamil Mosque, Bumen Hamlet, Bumirejo, Mojotengah, Wonosobo, it was a practice of exchanging waqf land at the Al Jamil Mosque and the land of one of the residents as an extension of the Abdurrahman Mosque. The reason for this exchange is to maintain the continuity of the benefits and objectives of the Al Jamil mosque waqf because the mosque is not well managed. Second, when viewed from the perspective of Imam Syafi'i this practice is not in accordance with Islamic law stipulated by Imam Syafi'i. In his opinion, the practice of back-and-forth is not allowed. The stated permissibility of swapping is not a law, but only as an alternative so that the sustainability of the benefits is not lost (more maslahah).